USED OIL RECYCLING AND TREATMENT IN THE UNITED ARAB EMIRATES ECONOMICAL AND ENVIRONMENTAL ASSESSMENTS - Hamad, Ahmad (2020)
In this work, we are investigating used oil recycling opportunities in United Arab Emirates. The economical assessment shows that it is worthy to recycle used oil. In the Emirate of Sharjah alone, recycling used oil could save $168,000 per year in fuel, or 250,000 gallons of base oil. The environmental assessment shows that more than 50% of used oil generated in the Emirate of Sharjah is not recorded. This is a serious problem that threatens our natural resources such as water and soil. Laboratory analysis of some properties of different classes of engine oils shows that recycling used oil could be pursued effectively.